2023
DOI: 10.1002/jhm.13103
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to improve diagnosis in emergency transfers to the pediatric intensive care unit

Abstract: Background: Late recognition of in-hospital deterioration is a source of preventable harm. Emergency transfers (ET), when hospitalized patients require intensive care unit (ICU) interventions within 1 h of ICU transfer, are a proximal measure of late recognition associated with increased mortality and length of stay (LOS).Objective: To apply diagnostic process improvement frameworks to identify missed opportunities for improvement in diagnosis (MOID) in ETs and evaluate their association with outcomes.Design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Indeed, in a recent study at our institution, we used a diagnostic improvement framework to analyze emergency transfers (ETs) to the PICU—escalation events in which patients require initiation of inotropes, intubation, and/or 60 cc/kg of intravenous fluid boluses within 1 hour of transfer from a ward to an ICU. 11 , 12 , 13 We demonstrated that diagnostic errors were common among ETs and thus may contribute to both delayed recognition of deterioration and adverse patient outcomes associated with this delay. 1 , 13 …”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, in a recent study at our institution, we used a diagnostic improvement framework to analyze emergency transfers (ETs) to the PICU—escalation events in which patients require initiation of inotropes, intubation, and/or 60 cc/kg of intravenous fluid boluses within 1 hour of transfer from a ward to an ICU. 11 , 12 , 13 We demonstrated that diagnostic errors were common among ETs and thus may contribute to both delayed recognition of deterioration and adverse patient outcomes associated with this delay. 1 , 13 …”
Section: Introductionmentioning
confidence: 85%
“… 11 , 12 , 13 We demonstrated that diagnostic errors were common among ETs and thus may contribute to both delayed recognition of deterioration and adverse patient outcomes associated with this delay. 1 , 13 …”
Section: Introductionmentioning
confidence: 85%
“…5 Lastly, a single-center retrospective study of pediatric patients who experienced emergent transfer to the intensive care unit, a proximal measure for late recognition of clinical deterioration, found that 29% had missed opportunities for improvement in diagnosis. 6 Not surprisingly, these patients had higher mortality rates and longer posttransfer lengths of stay.…”
Section: Estimates Vary Widely Depending On the Measurement Strategy ...mentioning
confidence: 94%